The Conditions for Hearing a Dispute in Islamic Jurisprudence:Review of Article 84 (3) and Articles 5-11 of Iranian Civil Procedure Code - Khierollah Hormozy (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2016)
Articles 5 and 7-11 of the Civil Procedure Code have been influenced by Islamic jurisprudence. Articles 7-11 did not exist in the previous version of the Civil Procedure Code. In Islamic jurisprudence, these and other issues are regarded as conditions for hearing the dispute. Iranian legislator has, however, treated theses issues as objections and obstacles to hearing the dispute. In the event of lacking these conditions, the dispute cannot be heard and the court must issue an order for not hearing the case. This is contrasted with a declined order. The aim of this article is to examine the conditions for a dispute to be heard in Islamic jurisprudence and compare Iranian Civil Procedure Code with French law.